2019
DOI: 10.1177/0037549718825303
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of dispersion and distribution behaviors of hydrogen leakage in the garage with a crossbeam

Abstract: A three-dimensional computational fluid dynamics simulation model resolved by the unsteady Reynolds-Averaged Navier–Stokes equations was developed to predict hydrogen dispersion in an indoor environment. The effect of the height of the crossbeam (Hc) on hydrogen dispersion and distribution behaviors in a four-car garage was numerically investigated under fully confined and natural ventilation conditions. For the fully confined condition, the garage was almost completely filled with a flammable hydrogen cloud a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition, smoke barriers are often installed in existing large underground garages to limit the spread of smoke, but in the event of hydrogen leakage it can cause a localized increase in hydrogen concentration [3]. Li et al [4] found that the volume ratio of the flammable region in a closed garage tends to increase as the beam height increases; after setting two symmetrical natural vents, the flammable volume ratio decreased by 50%. Merilo et al [5] found that mechanical ventilation resulted in a significant reduction in hydrogen concentration and overpressure from deflagration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, smoke barriers are often installed in existing large underground garages to limit the spread of smoke, but in the event of hydrogen leakage it can cause a localized increase in hydrogen concentration [3]. Li et al [4] found that the volume ratio of the flammable region in a closed garage tends to increase as the beam height increases; after setting two symmetrical natural vents, the flammable volume ratio decreased by 50%. Merilo et al [5] found that mechanical ventilation resulted in a significant reduction in hydrogen concentration and overpressure from deflagration.…”
Section: Introductionmentioning
confidence: 99%
“…The number of the vents is crucial to the ventilation. The compartment with two vents were proposed to enhance the efficiency of ventilation [14][15][16][17][18]. Saikili et.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the location of vents dominates partially the pattern of flow. Li et al [16] set up two symmetric ventilation openings to investigate the vertical dispersion and distribution behaviors of the hydrogen, and results showed that the volumetric ratio of the flammable region decreased by 50% at t=600 s.…”
Section: Introductionmentioning
confidence: 99%